THE INFLUENCE OF CONVERSION MODEL CHOICE FOR EROSION RATE ESTIMATION AND THE SENSITIVITY OF THE RESULTS TO CHANGES IN THE MODEL PARAMETER - Nita Suhartini (Universitas Gadjah Mada, 2006)
A study of soil erosion rates had been done on a slightly and long slope of cultivated area in Ciawi - Bogor, using 137Cs technique. The objective of the present study was to evaluate the applicability of the 137Cs technique in obtaining spatially distributed information of soil redistribution at small catchment. This paper reports the result of the choice of conversion model for erosion rate estimates and the sensitive of the changes in the model parameter. For this purpose, small site was selected, namely landuse I (LU-I). The top of a slope was chosen as a reference site. The erosion/deposit rate of individual sampling points was estimated using the conversion models, namely Proportional Model (PM), Mass Balance Model 1 (MBM1) and Mass Balance Model 2 (MBM2). A comparison of the conversion models showed that the lowest value is obtained by the PM. The MBM1 gave values closer to MBM2, but MBM2 gave a reliable values. In this study, a sensitivity analysis suggest that the conversion models are sensitive to changes in parameters that depend on the site conditions, but insensitive to changes in parameters that interact to the onset of 137Cs fallout input.